Metabolites of Microbial Origin with an Impact on Health: Ochratoxin A and Biogenic Amines - Russo, Pasquale; Capozzi, Vittorio; Spano, Giuseppe; Corbo, Maria R.; Sinigaglia, Milena; Bevilacqua, Antonio (Frontiers in Microbiology, 2016)
Safety and quality are significant challenges for food; namely, safety represents a big threat all over the world and is one of the most important goal to be achieved in both Western Society and Developing Countries. Wine safety mainly relies upon some metabolites and many of them are of microbial origin. The main goal of this review is a focus on two kinds of compounds (biogenic amines and mycotoxins, mainly ochratoxin A) for their deleterious effects on health. For each class of compounds, we will focus on two different traits: a) synthesis of the compounds in wine, with a brief description of the most important microorganisms and factors leading this phenomenon; b) prevention and/or correction strategies and new trends. In addition, there is a focus on a recent predictive tool able to predict toxin contamination of grape, in order to perform some prevention approaches and achieve safe wine.